Inserting ELSA application in Hybrid Learning to Enhance the Students’ Motivation in Speaking - Nur Aeni; Nur Fitri S; Hasriani Hasriani; Asriati Asriati (Har Press Indonesia, 2021)
The views of students and instructors are vital in developing a comfortable English learning environment. Hybrid learning with inserting the artificial intelligence is one way to attract the students’ attention in the classroom. The aim of this study is to investigate the how students’ motivation toward the using of ELSA application in Speaking. It investigated how the students engage in the classroom and their motivation. The mix approach was used in this study. The information gathered from the questionnaire about students' and lecturers' attitudes toward online learning materials. Using a Likert scale, they were graded. The responses of the students to online learning by applying ELSA application. The students were enthusiastic and engaged in learning Intensive Speaking by using ELSA application. The findings of this study are expected to aid teachers and lecturers in gaining insights and prior knowledge when designing ELT model for hybrid class. It is also intended to provide feedback on how to enhance the hybrid learning process.